Mathematics higher level : statistics - Harcet, Josip; Heinrichs, Lorrainrichs; Mariz Seiler, Palmira; Torres Skoumal, Marlene (Oxford : Oxford University Press, 2014)
Written by experienced IB workshop leaders, this book covers all the course content and essential practice needed for success in the Statistics Option for Higher Level. Enabling a truly IB approach to mathematics, real-world context is thoroughly blended with mathematical applications, supporting deep understanding and confident thinking skills.
Keywords: Cumulative distribution function; Expectation algebra and central limit theorem; Exploring statistical analysis methods Estimators and estimates; Hypothesis testing